2022
DOI: 10.3390/ijms232012409
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Count as Atrioventricular Block (AVB) Predictor following Pediatric Heart Surgery

Abstract: Neutrophils play a significant role in immune and inflammatory reactions. The preoperative inflammatory activation may have a detrimental effect on postoperative outcomes. The aim of the study was to investigate the relation between preoperative hematological indices on postoperative complications’ risk in pediatric cardiac congenital surgery. The retrospective single center analysis included 93 pediatric patients (48 (65%) males and 45 (35%) females), mean age of 7 (3–30) months referred for cardiac surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…27 Preoperative neutrophil count has been proposed as a predictive factor for postoperative atrioventricular block in pediatric cardiac surgery. 28…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
“…27 Preoperative neutrophil count has been proposed as a predictive factor for postoperative atrioventricular block in pediatric cardiac surgery. 28…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
“…Several studies in adult and paediatric surgery and medical therapy have demonstrated the significant value of simple blood analysis in predicting short-term and long-term outcomes [7][8][9][10]. The RDW is a simple, routinely analysed blood measurement which denotes the variability in red blood cell (RBC) size.…”
mentioning
confidence: 99%